PEMETAAN KOROSIFITAS ATMOSFER MENGGUNAKAN LOGAM BAJA KARBON RENDAH DAN KARBON TINGGI PADA WILAYAH KOTA SURABAYA - Rohmannudin, Tubagus Noor; Noerochim, Lukman; Sulistijono, Sulistijono; Achly, Fariza Hafizh; Tanjung, Rifqi Aulia (Jurnal Rekayasa Mesin, 2023)
Corrosion of metals is inevitable. One of the factors that affect corrosion is environmental conditions that contain pollutants like SO2, NO2, and Cl- which are found in many industrial and seaside areas. Surabaya is an area that has 2 types of conditions. In addition, Surabaya is the capital of the province where infrastructure development is running rapidly. Thus, this study maps the level of atmospheric corrosion in five areas in Surabaya by collecting corrosion rate data for 4 months with weight loss method using AISI 1020 Steel and SK5 Steel as test metals. XRD and SEM-EDX tests were conducted to compare the corrosion results. The average corrosion rate of low carbon steel was 0,6561 mpy and high carbon steel was 1,2523 mpy. The results concluded that the high level of atmospheric corrosivity of low carbon steel is in Sukomanunggal, Bulak, Rungkut, Pakal, Krembangan, and Bubutan sub-districts. The medium level is in Tegalsari, Gubeng, Tenggilis Mejoyo, Karang Pilang, Jambangan, Sawahan, and Dukuh Pakis sub-districts. The low level is in Lakarsantri, Mulyorejo, Simokerto, Sambikerep, Genteng, and Wonokromo sub-districts. Meanwhile, high atmospheric corrosivity levels for high carbon steel are in Krembangan, Karang Pilang, Bulak, Tenggilis Mejoyo, Pakal, and Jambangan sub-districts. The medium level is in Rungkut, Sawahan, Bubutan, Wonokromo, Tegalsari, Sukomanunggal, and Lakarsantri sub-districts. The level is in Dukuh Pakis, Genteng, Gubeng, Simokerto, Sambikerep, and Mulyorejo sub-districts. This mapping is based on the level of corrosion in each sub-district which is influenced by the presence of industry and its geographical location.